Extraction of valuable metals from acid mine drainage by an electrochemically activated limestone system - Weiquan Li; Junqi Wang; Zhengshuo Zhan; Jiayu Luo; Dongmei Zhou; Yang Lei (Nature Communications)
Abstract Acid mine drainage (AMD) contains toxic yet valuable heavy metals. Conventional chemical neutralization using hydrated lime is highly efficient in mitigating heavy metal pollution, yet it generates hazardous solid wastes and is inefficient in recovering critical metal resources. Here, we report the design and demonstration of an electrochemically activated limestone (EAL) system for AMD treatment and valuable metal extraction. The EAL system extracted 82.3-100.0% of different metals (Cu, Cd, Zn) with high purity (~81.3 wt% valuable metals) through electro-reduction and local high pH-mediated precipitation when treating simulated AMD with varied conditions and actual AMD at energy consumption of 0.006-0.180 kW·h g−1 metal. In addition, the effluent after the EAL treatment contains high alkalinity and Ca2+, which is proven to have CO2 sequestration potential. Overall, the EAL treatment reduces total costs by 17.9% and CO2 emissions by 60.1% compared to conventional lime dosing treatment, demonstrating its economic viability and ecological superiority for the practical remediation of AMD and extraction of valuable metals.